RONC-13. OUTCOMES OF RE-IRRADIATION IN PEDIATRIC PATIENTS WITH RECURRENT CNS TUMORS. Issue 2 (22nd June 2018) - Chang, Andrew; Vonbergen, Jayne; Fitzek, Markus; Thornton, Allan; Shih, Chie-Schin; Pradhan, Kamnesh
Abstract: Pediatric patients with recurrent CNS tumors have limited options. Published data with limited follow-up suggests that patients with >12 months interval after initial radiation may undergo a second course of radiation therapy. METHODS: Eleven pediatric patients (median age 3.3 years at initial irradiation) with a CNS tumor previously treated with definitive RT to a median dose of 55.8 Gy (50.4 – 59.4 Gy) were re-irradiated to the same area. RESULTS: Second course of definitive RT delivered additional 36.0 – 66.6 Gy after local failure (n = 7), combined local and leptomeningeal metastatic failure (n = 3), or new primary (n=1). Re-irradiation was given in daily fractioned radiotherapy at 1.8 Gy per fraction to focal fields only (n = 7), the craniospinal axis alone (n = 2), or with boost (n =2); one craniospinal patient also had an additional Gamma Knife boost. The median time between courses of irradiation was 44.3 months (12.8 – 267.9 months). The median total combined prescribed dose of radiation to the neural tissues was 109.8 Gy (90.0 – 126 Gy). With a median follow up time for survivors of 97.4 months (84.4 – 98.7 months) after re-irradiation, 5 patients have died from subsequent disease recurrence, 5 patients have no evidence of disease, and one patient has died from likely radiation necrosis. Three of the living patients had radiographic evidence of radiation changes that self-resolved. CONCLUSION: Re-irradiation in pediatric patients with recurrent CNS tumors can be safely done after a minimum12 month interval between times of irradiation.